Team Combat Identification: Effects of Gender, Spatial Visualization, and Disagreement. (June 2021) - Baker, Anthony L.; Keebler, Joseph R.; Anania, Emily C.; Schuster, David; Plummer, John P.
Objective: The combat identification (CID) abilities of same-gender and mixed-gender dyads were experimentally assessed, along with measures of spatial skills and team communication. Background: CID is a high-stakes decision-making task involving discrimination between friendly and enemy forces. Literature on CID is primarily focused on the individual, but the extensive use of teams in the military means that more team-based research is needed in this area. Method: After a set of training sessions, 39 dyads were tasked with identifying 10 armored vehicles in a series of pictures and videos. Team communication was recorded, transcribed, and coded for instances of disagreements. Results: Analyses indicated that males scored higher on a spatial visualization measure than did females. M-M teams performed significantly better than M-F teams on the CID task, but when spatial ability and team disagreements were added as predictors, the effect of team gender composition became nonsignificant. Spatial ability and team disagreement were significant predictors of team CID performance. Conclusion: Results suggest that spatial skills and team disagreement behaviors are more important for team CID performance than a team's gender composition. To our knowledge, this is the first lab study of team CID. Application: This research highlights the importance of understanding both individual differences (e.g., spatial skills) and team processes (e.g., communication) within CID training environments in the military context.